Modeling Human Capital Impact on the Development of the Iraqi Oil Industry - Ali et al. (Baghdad Science Journal, 2019)
Iraq has the second largest proven oil reserves in the world. According to oil experts, it is expected that the Iraq's reserves to rise to 200+ billion barrels of high-grade crude.